Can the Fitzroy River Declaration ensure the realisation of the First Law of the river and secure sustainable and equitable futures for the West Kimberley? - LIM, Michelle Mei Ling (Institutional Knowledge at Singapore Management University, 2017)
Threats to the unique cultural and ecological values of the river - events that led to the evolution and conclusion of the Declaration - legal and governance options for realising the objectives of the declaration - establishing a Indigenous Protected Area (IPA) - achieving sustainable and equitable futures in the West Kimberley - importance of harnessing momentum.